Fast transient fluorescence (FTRF) technique for monitoring free-radical crosslinking copolymerization (FCC) of styrene (S) with various divinylbenzene (DVB) contents - Pekcan, Ö.; Kaya, D. (Elsevier BV, 2001)
Abstract The gelation during free-radical crosslinking copolymerization (FCC) of styrene (S) and commercial divinylbenzene (DVB) in bulk was studied using Fast Transient Fluorescence (FTRF) technique. Pyrene (Py) was used as a fluorescence probe for the FTRF experiments. Fluorescence lifetimes of Py from its decay traces were measured and used to monitor the gelation processes in various DVB contents. Styrene consumption rates were measured during gelation process employing Stern-Volmer kinetic model. Composite rate constants, k r were determined for each DVB content experiments and it is observed that as DVB is increased k r increases.